Chronic neutrophilic leukaemia. - Gan, G.G.; Pasagna, J.F.; Eow, G.I.; Nadarajan, V.S. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2007)
Chronic neutrophilic leukaemia is a rare myeloproliferative disease characterised by splenomegaly, sustained neutrophilia, raised vitamin B12 level and absence of the Philadelphia chromosome. We report a 74-year-old man who presented first with Sweet's syndrome and subsequently leukocytosis. He had splenomegaly, a raised vitamin B12 level, serum uric acid and neutrophil alkaline phosphatase score. Cytogenetic study of the marrow was normal and peripheral blood for BCR-ABL gene transcript was not detectable. He subsequently passed away with bronchopneumonia.